Equality in Labor Regulations for People with Disabilities in Indonesia - Imma Indra Dewi W; Koleta Donna Indhayana Putri (West Science Law and Human Rights, 2026)
The right to work for persons with disabilities in Indonesia is regulated in Law No. 8 of 2016 concerning Persons with Disabilities. However, in reality, not all human resources have the same capacity, including persons with disabilities (different abilities). This poses challenges for persons with disabilities in entering the workforce. These challenges arise due to attitudes towards disability in society. Basically, society is still unable to be objective in accepting and assessing differences. Many of the requirements in the recruitment selection process in the world of work still focus on the physical and mental perfection of applicants. Based on human rights, all individuals are equal, and consequently, every individual has equality because, in essence, individuals are equal and have the same status as one another. Equality is a fundamental principle of human rights. With equality, individuals have equal dignity and worth. This research is normative legal research based on issues concerning equal employment regulations and efforts to strengthen equality in the formation of inclusive labor laws for persons with disabilities in Indonesia.